Perancangan dan Implementasi Website Profil Perusahaan di PT. Interpak Industries Batam - Andrew Cen; Herman Herman (National Conference for Community Service Project (NaCosPro), 2023)
Practical Work (KP) is one of the lecture programs that must be completed by students as one of their final assignments. With this practical work, the aim of educational institutions running the program is to provide real work experience to students. In carrying out this practical work, the author carries out service activities to PT. Interpak Industries Batam. The author has the opportunity to analyze and provide solutions to problems found by partner companies. The problem found by the author is the partner's company profile website being outdated. Therefore, the author will help partners by designing and implementing a more attractive and efficient company profile website for PT. Interpak Industries Batam. The design uses methods including data collection, design process, implementation process and valuation process. The results of the company profile website design will then be implemented live (hosting), so that partners and customers can directly access the website.